Does One Secure Their Own Salvation? Analysis on Continue to Work Out Your Salvation - Suparyadi, Zakharia; Hariyanto, Hariyanto; Siregar, Sahat; Tumbelaka-Wieland, Josephine Mariana (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2024)
Though conceptually different, Sayyed Hosein Nashr and Hans Kung's ideas on salvation share the same theological characteristics, which includes emphasizing the need of teaching kindness in order to achieve salvation. There is an inconsistency between this concept with the Bible. Luther believed that people are justified by faith and that this is the concept of salvation. What about the advice to "continue to work out your salvation" in Philippians 2:12? What type of salvation do believers achieve? Researchers are interested in gaining a comprehensive understanding of Philippians 2:12. The author notes that many members of the congregation lack a full grasp of the concept of salvation. This study aims to thoroughly explore the idea of "continue to work out your salvation" as presented in Philippians 2:12, employing qualitative methods such as textual and literary analysis. First, carry out in-depth text studies and observations on Philippians 2:12-18; secondly, build an exposition framework based on the collected data information. The research findings divide Philippians 2:12-18 into several components: a life of ongoing spiritual renewal (a transformative process encompassing spiritual growth, relational dynamics, and communal aspect) and a life that shines as a light (aligning with Jesus). Salvation is not stagnant but dynamic and demands active, progressive act. Good deeds stem from a proper response to the gifts received.